2020
DOI: 10.21037/tau.2019.12.20
|View full text |Cite
|
Sign up to set email alerts
|

Radical inguinal orchidectomy: the gold standard for initial management of testicular cancer

Abstract: Radical inguinal orchidectomy with division of the spermatic cord at the internal inguinal ring is the gold standard for diagnosis and local treatment of testicular malignancies. The technique is well established and described in detail in this paper, collating methods from various surgical textbooks and articles. We also discuss pre-operative considerations including fertility counselling and potential testicular prosthesis at time of orchidectomy, and the importance of contemplating differential diagnoses su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…Identify the gubernaculum and then clamp, divide, and ligate. Confirm the diagnosis with inspection [5]. Intravaginal torsion of the left testis was found to be rotated three times.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Identify the gubernaculum and then clamp, divide, and ligate. Confirm the diagnosis with inspection [5]. Intravaginal torsion of the left testis was found to be rotated three times.…”
mentioning
confidence: 68%
“…the skin 2 cm superior and parallel to the inguinal ligament, following the line connecting the internal and external rings. Continue the incision through the subcutaneous fat and the Camper and Scarpa fasciae [5]. Identify the external oblique fibers and external inguinal ring.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Radical inguinal orchiectomy is the standard surgical approach for testicular tumours 18 . We suggest that scrotal exploration following trauma may be inappropriate if a patient has a testicular tumour.…”
Section: Discussionmentioning
confidence: 98%
“…TSS exhibits a low recurrence rate in some STM 7 , 15 . Studies have reported that 60–70% of nonpalpable masses of less than 2 cm are nonmalignant lesions such as small benign Leydig or Sertoli cell tumors 2 , 3 , 16 18 . No difference was demonstrated in the cancer-specific survival between the RO and TSS groups in 5365 patients with tumors of less than or equal to 2 cm from the Surveillance, Epidemiology, and End Results database 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%